(untitled) (International Journal of Engineering Management Science, 2024)
Human survival depends on water, yet there is still a water shortage in many regions of the world. It is therefore imperative that we save water. One of the instruments for doing so may be this system. One of the sectors that use a lot of water is agriculture. The process of irrigation takes time, thus it needs to be completed on schedule. foundation. The article’s goal is to create an autonomous irrigation system that senses soil moisture and switches the water delivery system on and off on its own. The updated moisture content data in the proposed system is used to control the water pump. This paper will provide thorough understanding of the appropriate technique for better irrigation.